Pure androgen-secreting adrenal tumor (PASAT): A rare case report of bilateral PASATs and a systematic review - Liao, Zhangcheng; Gao, Yuting; Zhao, Yang; Wang, Zhan; Wang, Xu; Zhou, Jiaquan; Zhang, Yushi (Frontiers in Endocrinology, 2023)
Background Adult pure androgen–secreting adrenal tumors (PASATs) are extremely rare, and their characteristics are largely unknown. Methods A rare case of adult bilateral PASATs was reported, and a systematic literature review of adult PASATs was conducted to summarize the characteristics of PASATs. Results In total, 48 studies, including 40 case reports and 8 articles, were identified in this review. Analysis based on data of 42 patients (including current case and 41 patients from 40 case reports) showed that average age was 40.48 ± 15.80 years (range of 18-76). The incidence of adult PASAT peaked at 21-30 years old, while that of malignant PASAT peaked at 41-50 years old. Most PASAT patients were female (40/42, 95.23%), and hirsutism was the most common symptom (37/39, 94.87%). Testosterone (T) was the most commonly elevated androgen (36/42, 85.71%), and 26 of 32 tested patients presented increased dehydroepiandrosterone sulfate (DS) levels. In malignancy cases, disease duration was significantly decreased (1.96 vs. 4.51 years, P=0.025), and tumor diameter was significantly increased (8.9 vs. 4.9 cm, p=0.011). Moreover, the androgen levels, namely, T/upper normal range limit (UNRL) (11.94 vs. 4.943, P=0.770) and DS/UNRL (16.5 vs. 5.28, P=0.625), were higher in patients with malignancy. In total, 5 out of 7 patients showed an increase in DS or T in the human chorionic gonadotropin (HCG) stimulation test. Overall, 41 out of 42 patients (including current case) underwent adrenal surgery, and recurrence, metastasis, or death was reported in 5 out of 11 malignant patients even with adjuvant or rescue mitotane chemotherapy. Conclusion Adult PASAT, which is predominant in women, is characterized by virilism and menstrual dysfunction, especially hirsutism. Elevated T and DS may contribute to the diagnosis of adult PASAT, and HCG stimulation test might also be of help in diagnosis. Patients with malignant PASAT have a shorter disease duration, larger tumor sizes and relatively higher androgen levels. Surgery is recommended for all local PASATs, and Malignancy of PASAT should be fully considered due to the high risk of malignancy, poor prognosis and limited effective approaches.